Public Perception of the Use of Brokerage Services at the Kolaka Ferry Port: Experience, Selective, and Contextual Based - Rahmat Hidayat; Arafat Arafat; Widyawati Widyawati (Program Pascasarjana Universitas Negeri Makassar, 2021)
The existence of brokers in administrative services raises various perceptions among the public. Some people think that the presence of brokers as one of the negative image bearers of the organization, and some people perceive it as a positive thing. Therefore, this article is here to explain the public perception toward the use of brokers with the research located at Kolaka Ferry port. This research uses quantitative methods with data sources derived from the results of questionnaires and supported by secondary data related to the use of brokerage services and ticketing services at ports. The research data were then analyzed descriptively by percentage, starting with calculating the respondent's value for each aspect, recapitulating the value, calculating the average value, and calculating the presentation. The results showed that the people in Kolaka Regency felt happy and were helped by the presence of brokers. Unofficial ticket services are the reason people prefer to use brokerage services when buying tickets. Brokers who provide services will not be held responsible when people are caught using their services. In addition, the community supports the provision of punishment when a port manager is involved in the practice of brokering.